Amethyst Disputation (Datura Stramonium) As A New Type of Psychotropics - Purnomo Santoso, Adi; Nurdin, Boy (Journal of Management Economic and Financial, 2024)
The amethyst plant (Datura stramonium) contains various active compounds, amethyst is also often used as an alternative medicine. This plant is believed to cure bruises, wounds, toothache, fever, rheumatism, gout and asthma. However, amethyst also has toxic substances that can cause several dangerous symptoms if consumed. One of the most dangerous substances in amethyst is scopolamine which has more dangerous effects than marijuana, methamphetamine, ecstasy, heroin and cocaine. This plant can make humans look like zombies, causing hallucinations. Apart from that, it is often misused to create the effect of excessive pleasure or euphoria, this can cause addiction because users want to repeat the happy feeling as an addictive or psychotropic substance. The legal consequences for users of amethyst narcotics which are not registered in the law are currently unable to take legal action against users, because the narcotics law does not regulate the type of amethyst narcotics itself, therefore the police and the National Narcotics Agency are in charge cannot take legal action against amethyst users. Current community efforts are only in the form of (preventive) appeals and advocacy campaigns, outreach and stop drug campaigns for the community. So there needs to be encouragement from various parties to the legislative body so that there are changes to statutory regulations to determine amethyst as a new type of psychotropic.